2018
DOI: 10.1111/aji.12860
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles generated by placental tissues ex vivo: A transport system for immune mediators and growth factors

Abstract: A system of ex vivo placental villous and amnion tissues can be used as an adequate model to study placenta metabolic activity in normal and complicated pregnancies, in particular to characterize EVs by their surface markers and by encapsulated proteins. Establishment and benchmarking the placenta ex vivo system may provide new insight in the functional status of this organ in various placental disorders, particularly regarding the release of EVs and cytokines. Such EVs may have a prognostic value for pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 258 publications
0
35
0
Order By: Relevance
“…The placenta serves as the lungs, gut, kidneys, and liver of the fetus ( Burton and Jauniaux, 2015 ; Maltepe and Fisher, 2015 ). This fetal organ also has major biological actions that modulate maternal physiology ( Burton and Jauniaux, 2015 ; Sasaki and Norwitz, 2011 ; Taglauer et al, 2014 ; Fitzgerald et al, 2018 ) and, importantly, together with the extraplacental chorioamniotic membranes, shield the fetus against microbes from hematogenous dissemination and from invading the amniotic cavity ( Ander et al, 2019 ; Kwon et al, 2014 ). Indeed, most pathogens that cause hematogenous infections in the mother cannot reach the fetus, which is largely due to the potent protective mechanisms provided by placental cells (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The placenta serves as the lungs, gut, kidneys, and liver of the fetus ( Burton and Jauniaux, 2015 ; Maltepe and Fisher, 2015 ). This fetal organ also has major biological actions that modulate maternal physiology ( Burton and Jauniaux, 2015 ; Sasaki and Norwitz, 2011 ; Taglauer et al, 2014 ; Fitzgerald et al, 2018 ) and, importantly, together with the extraplacental chorioamniotic membranes, shield the fetus against microbes from hematogenous dissemination and from invading the amniotic cavity ( Ander et al, 2019 ; Kwon et al, 2014 ). Indeed, most pathogens that cause hematogenous infections in the mother cannot reach the fetus, which is largely due to the potent protective mechanisms provided by placental cells (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in EV-associated cytokines have been reported for several pathologies including infectious diseases 17,18,27 . Moreover, complex interconnections between groups of soluble and EV-associated cytokines have been found previously for several diseases 19,28 , but the content of EVs has not been systematically studied for CVD. Here, we studied the patterns of cytokines released as soluble molecules and in association with EVs in patients with the most severe form of CVD, the ST-elevation myocardial infarction (STEMI).…”
mentioning
confidence: 99%
“…We next sought to explore the effects of our treatment in mediating (1) LRA induced EV-associated cytokine release (TNF-α or membrane-bound TNF-α), (2) translation of viral proteins (Pr55, p41, and p24), and (3) EV release. It is important to examine cytokines in association with EVs as recent findings have described a system of EV-associated pro-inflammatory cytokines, which has been shown to mediate cell-cell communication in multiple viral infections [ 22 , 24 , 45 , 101 , 120 , 122 , 123 , 144 ]. In Figure 5 A, we examined EVs isolated by Nanotrap particles (NT80/82) from ACH2 and U1 cell supernatants.…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular vesicles (EVs) are membrane-bound structures released from numerous cell types, which have been shown to play an important role in cell–cell communication and in mediating viral pathogenesis [ 24 , 45 , 101 , 115 , 116 , 117 , 118 , 119 ]. EVs may be necessary for the transport of signaling molecules, such as cytokines [ 120 ], viral proteins [ 22 , 116 , 121 ], and cellular proteins [ 45 , 101 , 122 ], which may be found associated to the EV membrane or encapsulated as cargo [ 120 , 123 ]. We have recently shown that IR may have modulatory effects on the biogenesis, packaging of cargo, and secretion of EVs in another retrovirus, known as the Human T-cell Lymphotropic Virus Type-1 (HTLV-1) [ 45 ].…”
Section: Introductionmentioning
confidence: 99%